Living Hadis dan Moderasi Beragama : Analisis Toleransi Agama di Kota Manado, Sulawesi Utara - Imran, Muhammad Imran; Hasan, Nugraha; Mahmud, Basri (Al-Ulum, 2025)
This study aims to analyze the implementation of religious tolerance values through the concept of Living Hadith within the framework of religious moderation in Manado City, North Sulawesi. Using a qualitative approach with a case study method, data were collected through interviews with religious leaders, community figures, local residents, as well as observations of interfaith social and religious activities. The analysis integrates hadith texts with field findings to explore how hadith values on tolerance, non-violence, humanity, national commitment, and respect for local traditions are internalized and manifested in social practices. The findings indicate that these values are embedded in communal traditions such as Mapalus, religious celebrations, customary events, and interfaith harmony. The Interfaith Harmony Forum (FKUB) plays a significant role as a platform for dialogue and conflict prevention. This study affirms that the Living Hadith concept contributes to fostering inclusive tolerance and strengthening religious moderation in Manado.